Report of agricultural survery in the western state of Nigeria - Western State of Nigeria (Ibadan, Oyo state : Ministry of Economic Development, Statistics division, 1976)
The report in this issue covers only the rural agricultural population of the western state. The sample survey has been an exercise in the western state since 1972.
nmn 05/04/19
Loans
Keywords: Agriculture---Economics; Agricultural survey; Agricultural report; Western State of Nigeria